DAMPAK PETUGAS PENGATUR LALU LINTAS TERHADAP KINERJA SIMPANG 4 TAK BERSINYAL LEMBAH UGM, YOGYAKARTA - Verawanti Verawanti; Prima Juanita Romadhona (TEKNISIA, 2019)
The arrangement of peak traffic flow in unsignalized intersections usually carried out by illegal traffic wardens (PTR) and legal traffic wardens (PR).Additionally, traffic management implemented by PTR and PR only during peak hours. This research was executed in4 unsignalized Intersection at Agro street – Bougenville street (Lembah UGM), Sleman. The high traffic volume without the arrangement at the intersection caused traffic jam, so the performance level decreased. This study aimed to determine the impact of PTR and PR and find out alternative solutions at the intersection. The methods for obtaining primary data were by surveying traffic volume data, vehicle speed data, queue length data, driving behaviours andgeometry in the field. The data analysis in this study used VISSIM 9.0.The intersection condition without traffic management of wardenshad delay as much as 21,93 seconds with level of service (LOS) C. Intersections management with PTR produced a value of intersection delay was 30,02 seconds with level of service (LOS) D. Intersections management with PR produced a value of intersection delay was 29,20 seconds with level of service (LOS) D. This result showed that the performance of the intersections in all conditions were worse conditions. The alternative solution in this research was traffic signal with average delay value was 30,31 seconds with level of service (LOS) D. Hopefully, management intersections with traffic signals could reduce accidents risk at intersections.